Educators’ Preparation to Teach, Perceived Teaching Presence, and Perceived Teaching Presence Behaviors in Blended and Online Learning Environments - Gurley, PhD, RN, CNE, COI, Lisa E (Online Learning, 2018)
Teaching in blended and online learning environments requires different pedagogical approaches than teaching in face-to-face learning environments. How educators are prepared to teach potentially impacts the quality of instruction provided in blended and online learning courses. Teaching presence is essential to achieving student learning outcomes, yet previous research has focused on student perceptions of teaching presence. Therefore, the purpose of this mixed methods convergent parallel study was to explore educators’ preparation to teach, perceived teaching presence, and perceived teaching presence behaviors in blended and online learning environments. The study was designed to examine the differences in educators’ perceived teaching presence and preparation to teach in blended and online learning environments. An adapted Community of Inquiry Survey Instrument was used to measure faculty perceptions of teaching presence. Results indicated a statistically significant difference between perceived teaching presence of facilitation for faculty that completed certification courses in preparation to teach in blended and online learning environments, as compared to faculty that only received on-the-job training. Qualitative responses to corresponding interview questions supported the findings. The findings of this study provide information to university educators and administrators supporting the importance of faculty preparation specific to teaching in blended and online learning environments.